The Culture-bound Hierarchy of Manhood: An Overview of Hegemonic Masculinity and Subordinate Male Figures in Shall We DANSU? - Saravia Vargas, Juan Carlos (2010)
Although the concept of hegemonic masculinity was defined more than two decades ago, failure to consider the significance of cultural differences in the construction of maleness has led contemporary critics to misinterpret the Japanese vision of hegemonic masculinity. This analysis of the most significant male characters in the movie Shall We DANSU? highlights the cultural components that shape the represented masculinities and shows how the movie criticizes Western compulsive masculinity discourse defined by Charlebois.